Evaluation of a machine learning algorithm for up to 48-hour advance prediction of sepsis using six vital signs. (June 2019) - Barton, Christopher; Chettipally, Uli; Zhou, Yifan; Jiang, Zirui; Lynn-Palevsky, Anna; Le, Sidney; Calvert, Jacob; Das, Ritankar
Abstract: Objective: Sepsis remains a costly and prevalent syndrome in hospitals; however, machine learning systems can increase timely sepsis detection using electronic health records. This study validates a gradient boosted ensemble machine learning tool for sepsis detection and prediction, and compares its performance to existing methods. Materials and methods: Retrospective data was drawn from databases at the University of California, San Francisco (UCSF) Medical Center and the Beth Israel Deaconess Medical Center (BIDMC). Adult patient encounters without sepsis on admission, and with at least one recording of each of six vital signs (SpO2, heart rate, respiratory rate, temperature, systolic and diastolic blood pressure) were included. We compared the performance of the machine learning algorithm (MLA) to that of commonly used scoring systems. Area under the receiver operating characteristic (AUROC) curve was our primary measure of accuracy. MLA performance was measured at sepsis onset, and at 24 and 48 h prior to sepsis onset. Results: The MLA achieved an AUROC of 0.88, 0.84, and 0.83 for sepsis onset and 24 and 48 h prior to onset, respectively. These values were superior to those of SIRS (0.66), MEWS (0.61), SOFA (0.72), and qSOFA (0.60) at time of onset. When trained on UCSF data and tested on BIDMC data, sepsis onset AUROC was 0.89. Discussion and conclusion: The MLA predicts sepsis up to 48 h in advance and identifies sepsis onset more accurately than commonly used tools, maintaining high performance for sepsis detection when trained and tested on separate datasets. Highlights: Machine learning algorithm accurately predicts sepsis up to 48 h in advance. Algorithm performance is superior to commonly-used disease severity scoring systems. Algorithm performs well even when trained and tested on different patient populations. May lead to improved patient outcomes through early detection and intervention.